2006
DOI: 10.1042/bj20051675
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous production in Wolinella succinogenes and characterization of the quinol:fumarate reductase enzymes from Helicobacter pylori and Campylobacter jejuni

Abstract: The epsilon-proteobacteria Helicobacter pylori and Campylobacter jejuni are both human pathogens. They colonize mucosal surfaces causing severe diseases. The membrane protein complex QFR (quinol:fumarate reductase) from H. pylori has previously been established as a potential drug target, and the same is likely for the QFR from C. jejuni. In the present paper, we describe the cloning of the QFR operons from the two pathogenic bacteria H. pylori and C. jejuni and their expression in Wolinella succinogenes, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Anthelmintics that have been used to cure helminthic infections in animals and humans have bacteriostatic and bactericidal effects against some bacteria by inhibiting the Frd enzyme complex (44,(46)(47)(48). In the present study, we demonstrated that P. gingivalis Frd was inhibited by oxantel in a dose-dependent manner with an IC 50 of 2.2 M, and at 5 M, oxantel effectively abolished Frd activity in a cytoplasmic extract (Table 2).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Anthelmintics that have been used to cure helminthic infections in animals and humans have bacteriostatic and bactericidal effects against some bacteria by inhibiting the Frd enzyme complex (44,(46)(47)(48). In the present study, we demonstrated that P. gingivalis Frd was inhibited by oxantel in a dose-dependent manner with an IC 50 of 2.2 M, and at 5 M, oxantel effectively abolished Frd activity in a cytoplasmic extract (Table 2).…”
Section: Discussionsupporting
confidence: 52%
“…This is a much lower concentration than the previously determined MIC of 125 M, suggesting that entry into the cell is the limiting factor in growth inhibition (35). In addition, the P. gingivalis Frd was much more sensitive to oxantel inhibition than recombinantly expressed and purified C. jejuni and H. pylori Frd (48). Oxantel also inhibited the growth of the two other selected oral bacterial pathogens that are predicted to rely on Frd for catabolism.…”
Section: Discussionmentioning
confidence: 72%
“…The bacterium can also generate energy aerobically directly from molecular hydrogen with the help of a hydrogenase (40). Moreover, H. pylori is able to use fumarate as an electron acceptor (17,33). No redox regulator Fnr homolog which might regulate the Cbb3 terminal oxidase has been identified, implying that its expression is constitutive.…”
Section: Discussionmentioning
confidence: 99%
“…All these elements are predicted to be required for menaquinone-dependent succinate dehydrogenase activity (45). The fumarate reductase of W. succinogenes is capable of both specific enzymatic activity during succinate-dependent methylene blue reduction and benzyl viologen oxidation through fumarate reduction (26).…”
Section: Discussionmentioning
confidence: 99%